JARINGAN SYARAF TIRUAN MENGGUNAKAN ALGORITMA BACKPROPAGATION UNTUK MEMPREDIKSI PRESTASI SISWA - Fatmi Zola (Universitas Islam Kuantan Singingi, 2018)
Vocational High School Negeri 1 Bunga Raya (SMK N 1 Bunga Raya) is a vocational school in the field of Multi Competency. Currently there are 265 students with 5 majors (field) including Computer Network Engineering (TKJ), Motorcycle Engineering (TSM), Accounting, Agricultural Processing Technique (TPHP), Plantation Agribusiness (ATP) .To improve student achievement, then schools provide scholarships in the form of academic achievement scholarships. Artificial Neural Network System using Backpropagation method applied in this research to predict student achievement, and expected to help solve the problem of giving scholarship to student achievement. Implemented using Matlab as a supportive software. With the value of School examination as training data and testing. The result of testing with architectural pattern 4-2-1, the data into two parts that is 20 training data with percentage error 95,6%. And 20 test data with 100% error percentage. The smaller the level of accuracy error used will be the smaller deviation results Artificial Neural Network with the desired target.